Infraclavicular Block With Lateral Approach and Nerve Stimulation: Extent of Anesthesia and Adverse Effects. Issue 1 (1st January 2002) - Jandard, C.; Gentili, M. E.; Girard, F.; Ecoffey, C.; Heck, M.; Laxenaire, M. C.; Bouaziz, H.
Abstract : Background and Objectives: The infraclavicular approach to the brachial plexus is little used despite theoretical advantages of the technique. Using a vertical paracoracoid approach, we assessed the extent of the sensory block and the incidence of adverse effects. Methods: After obtaining informed consent, 100 patients undergoing surgical procedures distal to the elbow were evaluated. The block was performed using a peripheral nerve stimulator. The puncture site was located in the infraclavicular fossa; the direction of the insulated needle was perpendicular to the skin. Motor response was sought in the hand or wrist at ≤ 0.6 mA. A total of 40 mL of 1.5% mepivacaine was administered as a single injection. The sensory block was evaluated every 5 minutes for 30 minutes before surgery in the cutaneous distribution of terminal branches of the brachial plexus. Results: When one considers the cutaneous distributions of the median, ulnar, radial, and musculocutaneous nerves, the success rate was 89% for surgery without need for additional peripheral nerve blocks or general anesthesia. In contrast, cutaneous areas innervated by the axillary and medial cutaneous nerves were rarely anesthetized. We were unable to demonstrate a correlation between the intensity of the stimulation and the success of the block. On the other hand, a correlation was found between tourniquet sensation and the absence of anesthesia of the medial cutaneous nerve of the arm. Local anesthetic toxicity, Horner's syndrome, and vascular puncture were respectively observed in 1%, 4%, and 5% of cases. The depth of the needle introduction was correlated with the body mass index ( P < .001; r = .63). Conclusion: Single injection infraclavicular block, using a vertical paracoracoid approach, appears suitable for surgery distal to the elbow. Selective anesthesia of the medial cutaneous nerve is useful in improving tolerance of the tourniquet.